Genetics and identification of markers linked to multiflorous spikelet in hexaploid oat - Pellizzaro,Kelly (2016)
Abstract The formation of naked grains is directly associated with the formation of multiflorous spikelets in oats. The objectives of this study were to determine the genetics of multiflorous spikelet and to identify molecular markers linked to this character in hexaploid oat. Genetic analysis for multiflorous spikelet was performed in the F5 and F6 generations of two oat populations. DNA extracted from F5:6 plants were assayed with 6,000 genome-wide single nucleotide polymorphism (SNP) markers using a genotyping platform developed for oat. Genetic analysis indicated the presence of a major gene controlling multiflorous spikelet in the UFRGS 01B7114-1-3 x UFRGS 006013-1 population. The SNP marker GMI_ES17_c5923_221 showed strong association with the multiflorous spikelet phenotype. These results suggest that the marker GMI_ES17_c5923_221 should be linked to a gene controlling multiflorous spikelet in the oat lines evaluated in this study.